2011
DOI: 10.1007/s13193-011-0119-x
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Sarcoma—Review of Experience at a Tertiary Care Cancer Centre

Abstract: This study is a retrospective analysis of prospective data base of soft tissue sarcoma (STS) maintained in the department of Surgical Oncology, Bhim Rao Ambedkar Institute Rotary Cancer Hospital (BRA-IRCH), All India Institute of Medical Sciences, which is a tertiary care cancer centre. A total of 300 patients of STS were treated between 1995 and 2006. The mean age at presentation was 40.6 years and males were more affected then females. Extremity sarcomas were more common than non extremity sarcoma and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…To solve the problem that few options exist for the treatment of advanced sarcomas, researchers are doing intensive work in this field. Because of the hypersensitivity of STS, targeted therapies with better tolerance and less side effects are quite promising (Shukla et al, 2011;Purohit et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To solve the problem that few options exist for the treatment of advanced sarcomas, researchers are doing intensive work in this field. Because of the hypersensitivity of STS, targeted therapies with better tolerance and less side effects are quite promising (Shukla et al, 2011;Purohit et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the study conducted by Shukla et al in India which showed that the mean age of patients at presentation was 40.6 years. 7 STS were more common in the lower extremity ( Figure 10). Table 8 shows the common histologic types of soft tissue sarcomas compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its management requires an experienced multidisciplinary team in an expert center (Faivre, & Le P echoux, 2013). They constitute about 1% of all solid tumors, (Shukla & Deo, 2011) and can occur in any part of the body (Umer, Umer, Qadir, Abbasi, and Masood, 2013). It present most commonly as an asymptomatic mass, and swelling was the presenting symptom in 96% patients (Shukla & Deo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They constitute about 1% of all solid tumors, (Shukla & Deo, 2011) and can occur in any part of the body (Umer, Umer, Qadir, Abbasi, and Masood, 2013). It present most commonly as an asymptomatic mass, and swelling was the presenting symptom in 96% patients (Shukla & Deo, 2011). Their biological behavior is characterized by local aggressiveness and tendency to hematogenous spreading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation